Prescriptions for medical research. I--Management within the Medical Research Council. Issue 6893 (19th June 1993) - Gillett, R; Harrow, J
Abstract : In their submission to the government in advance of the white paper on science policy in the United Kingdom the Medical Research Council commends the MRC's own approach to managing directly funded research. But a series of semi-structured interviews with the directors of some of the MRC's units suggests a gap between the MRC's model of managed research and the reality. Although such units are theoretically managed from MRC head office (and units are charged an overhead for this), in practice each unit runs its own affairs. Between major reviews average contact time with the head office contact person is seven hours a year. The first paper argues that a purchaser-provider split would recognise the benefits of decentralisation and allow units to bid for research funds from several sources, the successful ones guaranteeing their survival through a rolling series of research programmes. The second paper criticises the MRC's cumbersome peer review system. Reliance on outside experts atrophies the scientific skills of head office staff and builds delays into decision making. A purchaser-provider model would allow the head office scientific staff to act like commercial research and development managers, commissioning research, and using the outcome, rather than peer review, as a criterion for continued funding.